Dampak Pemasaran Ekologis Terhadap Strategi Keberlanjutan Hotel di Canggu, Bali: Peran Perilaku Wisatawan, Digitalisasi, dan Tata Kelola - I Wayan Rediyasa; Fadillah Manuhutu; Jeanny Pricilia Anneke W (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the factors influencing tourist behavior in choosing environmentally friendly accommodations in the Canggu area of Bali, using the CAC-MOA (Awareness, Attitude, Context - Motivation, Opportunity, Ability) theoretical approach. The method used was a qualitative approach using observation, in-depth interviews, and a literature review. This study focused on tourism industry players, domestic and international tourists, and environmentalists. The results indicate that although environmental awareness and attitudes are quite high, tourists' actual behavior in choosing sustainable accommodations is still influenced by contextual factors such as the availability of facilities, price, and promotion; as well as limited ability and opportunity due to greenwashing and a lack of reliable information. This study emphasizes the importance of more transparent communication strategies and increasing trust in environmentally friendly practices in the hospitality sector to encourage more sustainable tourist behavior.